Lipocalin-type prostaglandin D synthase: a glymphopathy marker in idiopathic hydrocephalus - Nishida, Namiko; Nagata, Nanae; Shimoji, Keigo; Jingami, Naoto; Uemura, Kengo; Ozaki, Akihiko; Takahashi, Makio; Urade, Yoshihiro; Matsumoto, Sadayuki; Iwasaki, Koichi; Okumura, Ryosuke; Ishikawa, Masatsune; et al. (Frontiers in Aging Neuroscience, 2024)
Idiopathic normal pressure hydrocephalus in elderly people is considered a form of glymphopathy caused by malfunction of the waste clearance pathway, called the glymphatic system. Tau is a representative waste material similar to amyloid-β. During neurodegeneration, lipocalin-type prostaglandin D synthase (L-PGDS), a major cerebrospinal fluid (CSF) protein, is reported to act as a chaperone that prevents the neurotoxic aggregation of amyloid-β. L-PGDS is also a CSF biomarker in idiopathic normal pressure hydrocephalus and significantly correlates with tau concentration, age, and age-related brain white matter changes detected by magnetic resonance imaging. To investigate this glymphopathy, we aimed to analyze white matter changes and contributing factors in vivo and their interactions ex vivo. Cerebrospinal tap tests were performed in 60 patients referred for symptomatic ventriculomegaly. Patients were evaluated using an idiopathic normal pressure hydrocephalus grading scale, mini-mental state examination, frontal assessment battery, and timed up-and-go test. The typical morphological features of high convexity tightness and ventriculomegaly were measured using the callosal angle and Evans index, and parenchymal white matter properties were evaluated with diffusion tensor imaging followed by tract-based spatial statistics. Levels of CSF biomarkers, including tau, amyloid-β, and L-PGDS, were determined by ELISA, and their interaction, and localization were determined using immunoprecipitation and immunohistochemical analyses. Tract-based spatial statistics for fractional anisotropy revealed clusters that positively correlated with mini-mental state examination, frontal assessment battery, and callosal angle, and clusters that negatively correlated with age, disease duration, idiopathic normal pressure hydrocephalus grading scale, Evans index, and L-PGDS. Other parameters also indicated clusters that correlated with symptoms, microstructural white matter changes, and L-PGDS. Tau co-precipitated with L-PGDS, and colocalization was confirmed in postmortem specimens of neurodegenerative disease obtained from the human Brain Bank. Our study supports the diagnostic value of L-PGDS as a surrogate marker for white matter integrity in idiopathic normal pressure hydrocephalus. These results increase our understanding of the molecular players in the glymphatic system. Moreover, this study indicates the potential utility of enhancing endogenous protective factors to maintain brain homeostasis.